Functional implications of novel human acid sphingomyelinase splice variants - Rhein, Cosima; Tripal, Philipp; Seebahn, Angela; Konrad, Alice; Kramer, Marcel; Nagel, Christine; Kemper, Jonas; Bode, Jens; Mühle, Christiane; Gulbins, Erich; Reichel, Martin; Becker, Cord-Michael; et al. (PLoS ONE, 2012)
Acid sphingomyelinase (ASM) hydrolyses sphingomyelin and generates the lipid messenger ceramide, which mediates a variety of stress-related cellular processes. The pathological effects of dysregulated ASM activity are evident in several human diseases and indicate an important functional role for ASM regulation. We investigated alternative splicing as a possible mechanism for regulating cellular ASM activity.We identified three novel ASM splice variants in human cells, termed ASM-5, -6 and -7, which lack portions of the catalytic- and/or carboxy-terminal domains in comparison to full-length ASM-1. Differential expression patterns in primary blood cells indicated that ASM splicing might be subject to regulatory processes. The newly identified ASM splice variants were catalytically inactive in biochemical in vitro assays, but they decreased the relative cellular ceramide content in overexpression studies and exerted a dominant-negative effect on ASM activity in physiological cell models.These findings indicate that alternative splicing of ASM is of functional significance for the cellular stress response, possibly representing a mechanism for maintaining constant levels of cellular ASM enzyme activity.
EVALuna2:4672